SPASIAL EKONOMI, KEPADATAN KOTA, DAN KETINGGIAN BANGUNAN: STUDI KASUS HONGKONG - Suartika, Gusti Ayu Made (Universitas Gunadarma, 2007)
Tulisan ini mendiskusikan bagaimana isu ketinggian bangunan dan kepadatan wilayahdiregulasi dalam kebijakan perencanaan dan praktek-praktek terkait. Paper ini merefleksikantantangan yang dihadapi oleh beragam daerah, khususnya perkotaan, dalamperkembangannya saat ini maupun di masa yang akan datang. Sementara daerah perkotaanmemiliki keterbatasan skala keruangan, mereka diharapkan memiliki kemampuanmengakomodasi pertumbuhan populasi yang berkelanjutan, serta kompleksitas aktivitas,seiring tahapan pembangunan. Dengan menerapkan metode penelitian hermeneutic danmengambil Hongkong sebagai studi kasus, penelitian ini menekankan jika pada kondisitertentu, konsolidasi dan perencanaan daerah berkepadatan tinggi merupakan sebuahkeharusan, jika bukan keputusan perencanaan yang paling tepat. Beranjak dari pandangandimana keterbatasan lahan diopsikan sebagai faktor pendorong utama, dari yangkelihatannya sebagai pelonggaran pembatasan ketinggian bangunan di Hongkong,artikel ini menginvestigasi faktor-faktor intrinsik yang juga memiliki peranan penentu.Dalam mengilustrasikan argumentasinya, dikaji beragam strategi perencanaan terkait,yang diberlakukan di Hongkong, kondisi positif dan tantangan dalam implementasinya,termasuk permasalahan lingkungan yang muncul. Beragam kebijakan dan praktek yangdihasilkan dari prosedur ini diharapkan akan memberlakukan keseluruhan elemenelemenpenentu diatas sebagai satu kesatuan. Hanya dengan mensinergikan mereka,pembangunan berkelanjutan akan bisa diraih, seperti secara berulang ditekankan dalamdokumen Perserikatan Bangsa-Bangsa, Burtland Report (1983).AbstractThis article discusses how issues of density and building height are regulated within urbanplanning policies and practices. It reflects challenges encountered by many cities intheir current and potentially future development. While urban areas possess limited scaleof spatial resources, they are expected to have all the capacity to accommodate the continuallygrowing population, as well as intensity and complexity of the existing diverseactivities, taking place in line with their development stages. By using her-meneuticalresearch method and taking Hongkong as a case study, this paper emphasizes that tocertain cases consolidation and a high density approach is a must, if not the mostappropriate planning decision. Moving from an opinion in which limited spatialresources is viewed as the main motivator of the seemingly relaxed current buildingheight restriction in Hongkong, this paper further investigates intrinsic factors whichequally have determining roles. In illustrating its arguments, this article examinesrelevant urban planning strategies that have been enforced in Hongkong, pros and consfor their implementations, as well as arising environmental impacts the strategies haveinflicted. In measuring the appropriateness of similar strategies to other regions, such anendeavour requires preceding analysis of socio-cultural, economic, and political circumstancesof each given case. Added to this, an idealistic conception enforcing developmentas a process, which is not only accommodative to human basic, social, andeconomic needs, but also to the protection of the environment and nature, demands ahighlight (Chapin 1959, Godschalk, Keiser, Chapin 1997). As is often overlooked, thelater agenda should be consciously prioritised and imbedded within any planningapproaches. The anticipated policies and practices resulted out of this procedure areexpected to treat all these concerning matters as a unity. Only by synergizing them,sustainable development will be within our reach in the future, as are repeatedly viewedwithin the United Nation’s Burtland Report (1983).